Maize and pea germination and seedling growth responses to compost generated from biowaste of selected invasive alien plant species. Issue 1 (2nd January 2016) - Adam, Yusuf; Sershen,; Ramdhani, Syd
Abstract: Plant biowaste of alien species represents a potential resource for compost production. This study investigated the seed and seedling responses of maize and pea to composts generated from the biowaste of four invasive species in eThekwini, South Africa: Acacia podalyriifolia, Hedychium gardnerianum, Litsea glutinosa, and Tithonia diversifolia . Except for a 40% concentration of T. diversifolia, leachates of the biowaste from the four species had no marked effects on germination. In seedling growth studies, Berea Red soil (control) was supplemented with composts produced using combinations of the four species ( A. podalyriifolia + T. diversifolia [T1], A. podalyriifolia + H. gardnerianum [T2], L. glutinosa + T. diversifolia [T3], and L. glutinosa + H. gardnerianum [T4]), and a commercial compost (T5). Carbon and nitrogen levels of the biowaste composts were higher than the control, while their associated C/N ratios were low enough to encourage microbial growth, facilitate rapid decomposition, and support plant growth. A comparison of percentage seedling production, growth rate, and biomass production between the commercial compost and alien biowaste treatments revealed all parameters to be statistically comparable among T5, T1, and T3 for maize, and between T5 and T1 for pea. These superior biowaste composts did not enhance growth relative to the commercial compost, but supported growth to the same extent. However, N and P levels in T1 and T3 were lower than the commercial compost and appear to have altered biomass allocation patterns in both species relative to the commercial compost. The results suggest that there is potential to use invasive alien plant biowaste to improve soil for agricultural purposes.